PENGARUH TINGKAT PELAYANAN TERHADAP KEPUASAN PELANGGAN PT PLN (PERSERO) WILAYAH S2JB CABANG JAMBI (Studi Kasus Daya Di Atas 200 Kva) - Ahmad Tarmizi (Jurnal Ilmiah Universitas Batanghari Jambi, 2011)
This research was conducted by survey research methods, namely an attempt to obtain information from resfonden and concluded that a sample by using a structured questionnaire and patterned according to the needs of research. Sample as a source of research subjects was the customer power above 200 kVA. In this study, the studied population amounted to 137 customers, from the population is taken into the sample amounted to 55 customers or ± 40% of the entire population with an error rate of 5%. This is what writers do remember the limitations of time, effort and cost.To determine the level of customer satisfaction that is observed, it is used as a means of measuring Likert Scale. The model of the relationship equation between two variables, the equation obtained is called regression, linear regression equation can be shaped and to estimate a variable called the Dependent Variable and Independent Variables.The relationship between the variables X (technical services, payment points, and information) and Y variables correlated strongly positive at 0.902 (90.2 percent). Partially significant effect of variable X1. Where t value (7.109) is bigger than t table value (1.684) on the degree of confidence of 95 percent. While the X2 variables significant effect on variable Y. Where t (5.357) is bigger than t table (1.684) on the degree of confidence of 95 percent. And the X3 has a significant variable. Where t value (4.085) is bigger than t table (1.684) on the degree of confidence of 95 percent. Together the variable X has a significant influence on the variable Y. Where the calculated F value (73.994) is greater than F table (2.79).